A liver nodule in a patient transplanted for primary sclerosing cholangitis: an interdisciplinary diagnostic approach - Loosen, Sven Heiko; Schmeding, Maximilian; Roderburg, Christoph; Binnebösel, Marcel; Temizel, Ilknur; Mottaghy, Felix M.; Tischendorf, Jens J.W.; Tacke, Frank; Gaisa, Nadine T.; Hussein, Kais; Lehmann, Ulrich; Trautwein, Christian; Neumann, Ulf Peter; Luedde, Tom (Zeitschrift für Gastroenterologie, 2017)
We report the case of a 53-year-old female patient who was transplanted with the liver of a 71-year-old male donor for advanced primary sclerosing cholangitis (PSC) and who additionally was diagnosed with a histologically non-classifiable colitis shortly before transplantation. Upon follow-up abdominal ultrasound 4 months after transplantation, a liver lesion measuring 16 × 23 mm was detected in the transplanted liver. This lesion had not been noticed immediately after transplantation and showed a pattern suspicious for malignancy in contrast-enhanced ultrasound. In line, a biopsy revealed the presence of a metastasis of an adenocarcinoma of colorectal origin, suggesting that a colitis- and PSC-associated colorectal cancer of the recipient might have been overseen upon the initial diagnostic workup. Despite two negative follow-up colonoscopies, this hypothesis was further supported by a strong positive signal in projection to the cecum in a subsequently performed PET/CT-scan. However, surgical resection of the right colon that was performed simultaneously with the atypical resection of the liver metastasis only revealed an inflamed diverticulum but no malignancy in the resected colon segment. Moreover, cytogenetic and molecular genetic testing on the resected specimens clearly attributed the metastasis to the male donor. On the one hand, this case underlines the necessity of endoscopic surveillance of patients with PSC and/or inflammatory bowel disease as well as the challenges in diagnosis of colitis-associated cancer. On the other hand, it shows that the acceptance of organs from elderly donors in times of organ shortage might be linked to an increased risk of donor transmitted malignancies.
Keywords: Kontrastmittelsonografie; Lebertransplantation; erweiterter Organspenderkreis; primär sklerosierende Cholangitis (PSC); Colitis ulcerosa (CU); FISH-Analyse